Capsicum 2020
DOI: 10.5772/intechopen.91897
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effect of Capsaicin and Its Analogues

Abstract: Potent biomolecules from natural products from plants, animals, and minerals are the fundamental basis of the ailment of mankind. Capsicum or red pepper plants were grouped under the kingdom Plantae and family Solanaceae. It is used widely throughout the world in foods for their pungent flavor and aroma, and to prolong food spoilage. This chapter presents a frame of a concise compilation of the anticancer and cytotoxic potentials of Capsicum, its analogs, and related compounds. Capsaicin (trans-8-methyl-N-vani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…SAR studies involving 17 resulted in the synthesis of almost 30 synthetic analogs which were screened for growth-inhibitory activity using HeLa human ovarian carcinoma cells. 96 MTT assays revealed that four of these compounds, C-29 (18), CIDD-24 (19), CIDD-111 (20), and CIDD-99 (21), displayed the maximal decrease in cell viability of the HeLa cells over 24 h. The growth suppressive activities of 18, 19, and 21 were similar to each other (IC 50 < 5 μM) in HeLa cells. However, the growthinhibitory activity of 20 (IC 50 ∼ 25 μM) was lower than 18, 19, and 21.…”
Section: Anti-neoplastic Activity Of Capsaicin Region B Analogsmentioning
confidence: 86%
See 3 more Smart Citations
“…SAR studies involving 17 resulted in the synthesis of almost 30 synthetic analogs which were screened for growth-inhibitory activity using HeLa human ovarian carcinoma cells. 96 MTT assays revealed that four of these compounds, C-29 (18), CIDD-24 (19), CIDD-111 (20), and CIDD-99 (21), displayed the maximal decrease in cell viability of the HeLa cells over 24 h. The growth suppressive activities of 18, 19, and 21 were similar to each other (IC 50 < 5 μM) in HeLa cells. However, the growthinhibitory activity of 20 (IC 50 ∼ 25 μM) was lower than 18, 19, and 21.…”
Section: Anti-neoplastic Activity Of Capsaicin Region B Analogsmentioning
confidence: 86%
“…The vanilloid phytochemical 1 displays potent antineoplastic activity in multiple human cancers ,, and can improve the therapeutic efficacy of chemotherapeutic drugs and radiation therapy when used in combination. Despite such promising applications, the development of 1 as a clinically useful anticancer drug has been limited by its unpleasant side effects. The administration of 1 causes skin redness, hyperalgesia, nausea, intense tearing in the eyes, conjunctivitis, blepharospasm (sustained, forced, and involuntary closing of the eyelids), vomiting, abdominal pain, stomach cramps, bronchospasm, and burning diarrhea in patients. Clinical trials exploring the pain-relieving activity of 1 have shown that such side effects have resulted in patients discontinuing use of the drug.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A huge number of studies have demonstrated the capsaicin-mediated anticancer effects [ 122 , 123 ]. In non-small cell lung cancer (NSCLC), capsaicin inhibits vascular endothelial growth factor (VEGF) expression and angiogenesis via the p53-HIF1-VEGF pathway [ 124 ].…”
Section: Plants From Different Continents Used In Ethnomedicine For T...mentioning
confidence: 99%